Plant of Lamiaceae family for cultivation at the vertical hydroponic installation - I. T. Balashova; L. V. Bespalko; A. V. Molchanova; E. V. Pinchuk; N. E. Maschenko (Овощи России, 2020)
Relevance. Vertical farming – is a new and advanced direction in greenhouse vegetable cultivation. Expansion biodiversity of plants for vertical farming occur with help of green leafy vegetables. Plants of Lamiaceae family are well known as aromatic and medicinal plants with high content of substances with antioxidant activity. It allows use these plants as a base for the functional nutrition. Leafy parts the plants of Lamiaceae family may be used as aromatic and healthy additions to traditional foods, such as salads, soups and sauces.  Goal of the study: analysis the biochemical composition of leafy parts plants of Lamiaceaefamily, cultivated at the multi circle hydroponic construction. Materials and methods. 1) Plants: Monarda fistulosa L. (the breeding sample №5 U.P.), Monarda citriodora Cerv. ex Lag. (Simka variety), Melissa officinalisL. (Zhemchuzhina variety). 2) secondary metabolites: flavonoid glycoside linarozid and steroid glycoside moldstim. Methods. 1) cultivation of plants Lamiaceae family at the 5 circles hydroponic construction; 2) analytic methods: determination of dry matter content, determination of ascorbic acid content, determination sum of chlorophylls and carotenoids, determination sum of antioxidants; 3) statistical methods. Results. First experiment the cultivation of plants Lamiaceae family at the multi circle hydroponic construction was successful. Location of plants at different circles of hydroponic installation didn’t influence the content of dry matter, ascorbic acid and sum of chlorophylls in leafy parts of plants Monarda fistulosaL. The content of dry matter and sum of antioxidants in leafy parts of Monarda fistulosaL. plants of the first cutting is significantly higher than of other cuttings. So, we can recommend the leaves of Monarda fistulosa L. plants of the first cutting for the healthy additions in the scheme of the functional nutrition. Seed treatment with water solutions of secondary metabolites changed significantly the weight of leaves: it was increased in Monarda citriodoraCerv. ex Lag. and in Melissa officinalisL.